Association of China's two-child policy with changes in number of births and birth defects rate, 2008-2017 - Hanyi Chen; Ting Wei; Haiyin Wang; Yi Zhou; Hua Chen; Lianghong Sun; Shaotan Xiao; Wuren Ma; Huijuan Zhao; Guanghua Chen; Xinlei Liang; Donglan Zhang; et al. (BMC, 2022)
Abstract Background In October 2015, China's one-child policy was universally replaced by a so-called two-child policy. This study investigated the association between the enactment of the new policy and changes in the number of births, and health-related birth outcomes. Methods We used difference-in-difference model to analyse the birth record data in Pudong New Area, Shanghai.The design is descriptive before-and-after comparative study. Results The data covered three policy periods: the one-child policy period (January 2008 to November 2014); the partial two-child policy period (December 2014 to June 2016); the universal two-child policy period (July 2016 to December 2017). There was an estimate of 7656 additional births during the 18 months of the implementation of the universal two-child policy. The trend of monthly percentage of births to mothers aged ≥35 increased by 0.24 percentage points (95% confidence interval 0.19 to 0.28, p < 0.001) during the same period. Being a baby boy, preterm birth, low birth weight, parents with lower educational attainment, and assisted delivery were associated with a higher risk of birth defects. Conclusions The universal two-child policy was associated with an increase in the number of births and maternal age. Preterm birth, low birth weight, and assisted delivery were associated with a higher risk of birth defects, which suggested that these infants needed additional attention in the future.